2020
DOI: 10.5334/pb.502
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Role of Negative Emotions in the Origin and Control of Impulsive Actions

Abstract: This critical review elaborates on the origin of impulsive actions and how these can be controlled. We focus in particular on the role of negative events. First, we outline how impulsive actions often originate from negative events that are (emotionally) appraised. A discrepancy between this current state and a desired goal state leads to action tendencies. The urgency of the resulting action depends on the importance of the goal and the size of the discrepancy. Second, we discuss how such impulsive actions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…For example, Amsel [20] observed that hungry rats who were trained to obtain food in two runways ran faster in the second runway when they failed to obtain (the expected) food in the first runway. More generally, several theoretical frameworks assume an influence of such negative affective states on actions (for a review see [23]). For example, Frijda [24] suggests that events are appraised by individuals as pleasant or unpleasant, triggering states of action readiness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Amsel [20] observed that hungry rats who were trained to obtain food in two runways ran faster in the second runway when they failed to obtain (the expected) food in the first runway. More generally, several theoretical frameworks assume an influence of such negative affective states on actions (for a review see [23]). For example, Frijda [24] suggests that events are appraised by individuals as pleasant or unpleasant, triggering states of action readiness (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As such, changes in the SAT policy between the two contexts were engendered by manipulating the penalty size. However, even if error punishment is known to increase cautiousness (Potts 2011, Derosiere et al 2021b), as desired here, monetary losses also generate an emotional response (Carver 2006, Simoes-Franklin et al 2010, Frijda et al 2014, Eben et al 2020a), a sense of frustration increasing with the size of the loss (Gehring et al 2002, Holroyd et al 2004, Yeung and Sanfey 2004, Eben et al 2020c). Importantly, such negative emotion has been shown to induce a post-error acceleration of RTs rather than a slowdown (Purcell and Kiani 2016, Verbruggen et al 2017, Dyson et al 2018, Damaso et al 2020, Eben et al 2020c, Dyson 2021).…”
Section: Discussionmentioning
confidence: 76%
“…Within this framework, tendencies toward tremor are likely to covary to the greatest extent with motor impulsivity symptoms, though correlations with attentional symptoms are also possible (Cheyne et al, 2006). With respect to tasks thought to tap impulsive processes, one can distinguish phenomena such as delayed discounting (that relates to decision-making) from behavioral impulsivity itself (Eben et al, 2020) and motor control difficulties, as we have assessed them, should correlate more strongly with indices focused on behavior rather than decision-making. In summary, there are a variety of useful directions that could be pursued when linking motor control difficulties to other tasks and frameworks posited in the impulsivity literature.…”
Section: Discussionmentioning
confidence: 98%